Kajian Yuridis Tentang Berita Hoax Pada Media Sosial Ditinjau Dari UU ITE Nomor 11 Tahun 2008 - Rehulina Rehulina (Universitas Islam Sumatera Utara, 2018)
Abstract As part of information technology innovation, social media provides space for anyone to express their opinions and voice their thoughts, and so does it for society. Freedom to express opinions and thoughts or that of speech rights is the reason for hoax news maker to keep on spreading false news. Therefore, to prevent the spread of hoax news, the government, especially law enforcers, must give a warning in the form of strict sanctions for hoax news spreaders. The research method used in this research is normative juridical research method by which this research refers to the legal norms contained in the legislation. Normative juridical research was conducted by analyzing research problems through approaches to legal principles and referring to legal norms contained in regulations closely related to the subject matter. The imposition of sanctions on hoax news dissemination actors that contain elements of provocation, blasphemy of hatred that can cause insecurity and disintegration will be snared by Law Number 19 of 2016 amendment to Law Number 11 of 2011 concerning Electronic Information and Transactions and Book of Criminal Law (Law No.1 of 1946 concerning Criminal Law Regulations). Changes in technology provide convenience for everyone to do what they like and what they do not like. The use of internet networks and the large number of applications provide people to freely download the application and use it anytime. This change makes society an information society. The presence of social media makes the community in a process of communication that is not centralized, but spread. Therefore, the people must get knowledge about the right information or hoax news that contains racial or religious issues, disintegration and laws and regulations related to hoax news. Some things that can be done to help people understand about this hoax news are by holding seminars, interactive dialogues or FGDs. Keyword: Hoax, electronic information technology law, Social Media